Osteomyelitis of the Mandible Secondary to Impacted Third Molar - Appaji Athota; Rama Raju; Prabath; Ratnakar; Nagendra S Chunduri (Wolters Kluwer Medknow Publications, 2011)
Odontogenic infections resulting in osteomyelitis of the mandible are common. However, osteomyelitis of the coronoid process as a direct consequence of third molar infection is rare. The following report describes such a case in an 18-year-old female as a severe complication following third molar removal. Despite aggressive antimicrobial therapy and indicated treatment approach following microbiologic study, a severe osteomyelitis was present, clinically and radiographically. Finally, hemimandibulectomy, including exarticulation, was indicated to manage this severe complication.